2008 International Conference on Technology and Applications in Biomedicine 2008
DOI: 10.1109/itab.2008.4570536
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alcohol-dependent EEG on the traffic signal recognition

Abstract: Using EEG we studied the time course of the alcohol-effect on the traffic signal recognition. Results demonstrated the enhanced delta power of EEG in alcoholics. At 30 min after the ingestion of a moderate dose of alcohol, the accurate recognition rate for the traffic signal by alcohol-dependent subjects was significantly worse than controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Başar and Güntekin (2008) in their review on the major changes in brain oscillations in patients with alcoholism and those with genetic disorders, has reported the following effects: i) the reduction of amplitude in alcoholics while taking VEP signal during a visual oddball task (Jones et al, 2006); ii) increase in α, β coherence (Winterer et al, 2003); and iii) increased variation in low voltage α waves (Enoch et al, 1999). Further, Wang et al (2008) studied the time course of the alcohol-effect on the traffic signal recognition and showed the enhanced delta power of EEG in alcoholics. Studies also have shown a reduced activity in δ, θ, α1 bands and P300 amplitudes of the off springs of alcoholics as compared to age matched controls (Kamarajan et al, 2006;Rangaswamy et al, 2007).…”
Section: Reduction In the Amplitude Of Error Related Negativity (Ern)mentioning
confidence: 99%
“…Başar and Güntekin (2008) in their review on the major changes in brain oscillations in patients with alcoholism and those with genetic disorders, has reported the following effects: i) the reduction of amplitude in alcoholics while taking VEP signal during a visual oddball task (Jones et al, 2006); ii) increase in α, β coherence (Winterer et al, 2003); and iii) increased variation in low voltage α waves (Enoch et al, 1999). Further, Wang et al (2008) studied the time course of the alcohol-effect on the traffic signal recognition and showed the enhanced delta power of EEG in alcoholics. Studies also have shown a reduced activity in δ, θ, α1 bands and P300 amplitudes of the off springs of alcoholics as compared to age matched controls (Kamarajan et al, 2006;Rangaswamy et al, 2007).…”
Section: Reduction In the Amplitude Of Error Related Negativity (Ern)mentioning
confidence: 99%
“…Appropriate selection of EEG signal channel can significantly reduce the computational complexity and computation time. [ 16 17 ]…”
Section: Introductionmentioning
confidence: 99%
“…Among these techniques, electroencephalography (EEG) is a reliable and significant method of measuring neurophysiological activity in the human brain and the psychological state of drivers when driving. Using advanced data mining techniques, the EEG signal can be utilized to identify a driver’s alertness (Chuang et al, 2015), to predict the distraction (Wang et al, 2015), to study a driver’s perception of signal lights (Wang et al, 2008), to monitor a driver’s driving states (Peng and Wu, 2009), and to predict a driver’s intention to emergency brake (Kim et al, 2014).…”
Section: Introductionmentioning
confidence: 99%